1999
DOI: 10.1093/jnci/91.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Marital Stability After Breast Cancer

Abstract: For the times studied, breast cancer does not appear to be associated with marital breakdown among Quebec women. Marital difficulties occurred mainly among the small proportion of women who probably already had marital difficulties when diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 12 publications
4
46
2
6
Order By: Relevance
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have in fact suggested that men are less able to undertake a caregiving role and assume the burdens of home and family maintenance compared with women. [3][4][5][6][7][8][9][10][11] Thus, a woman becomes willing sooner in the marriage to commit to the burdens of having a sick spouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, research has revealed that most couples adapt well and have sufficient resources to cope with illness (Dorval et al, 2005;Taylor-Brown, Kilpatrick, Maunsell, & Dorval, 2000). Most couples do not report a decrease in the quality of their marital relationship (Manne, 1998), and only a small proportion of couples experience difficulties or separation following diagnosis (Dorval, Maunsell, Taylor-Brown, & Kilpatrick, 1999;Taylor-Brown et al, 2000). In addition, many couples report a strengthening of their relationship (Dorval et al, 2005;Hinnen et al, 2008) and the occurrence of positive changes or relational growth after this experience (Weiss, 2004).…”
Section: The Partner Experience Of Breast Cancermentioning
confidence: 99%
“…Es decir, por la manera en la cual acostumbraban comunicar y compartir sus sentimientos, por el grado de flexibilidad que mostraban en la organización y distribución de actividades y responsabilidades, y por las condiciones de respeto, indiferencia o agresión que ya eran una característica de la relación. Una mala adaptación conyugal en el momento del diagnóstico permite predecir una mayor probabilidad de experimentar dificultades a este nivel (102,103) . Por otro lado, hay autores que incluso sugieren que pueden ocurrir mejoras en la calidad de la relación, y una mayor aproximación emocional entre la pareja, después de un diagnóstico de cáncer (102,104) .…”
Section: Discussionunclassified